2019
DOI: 10.1186/s13613-019-0526-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of left ventricular ejection fraction and a novel method to improve its assessment of myocardial contractility

Abstract: Background The aim of this study was to quantify the impact of different cardiovascular factors on left ventricular ejection fraction (LVEF) and test a novel LVEF calculation considering these factors. Results 10 pigs were studied. The experimental protocol consisted of sequentially changing afterload, preload and contractility. LV pressure–volume (PV) loops and peripheral arterial pressure were obtained before and after each intervention. LVEF was calculated as stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Hypovolemia has also been implicated in HDLVEF development (24), although we found no difference in net fluid balance or IV fluid input between LVEF cohorts. Furthermore, previous studies have demonstrated that large variations in preload did not influence LVEF (14). Impaired LV relaxation may reduce preload, resulting in a compensatory hyperdynamic state.…”
Section: Discussionmentioning
confidence: 94%
“…Hypovolemia has also been implicated in HDLVEF development (24), although we found no difference in net fluid balance or IV fluid input between LVEF cohorts. Furthermore, previous studies have demonstrated that large variations in preload did not influence LVEF (14). Impaired LV relaxation may reduce preload, resulting in a compensatory hyperdynamic state.…”
Section: Discussionmentioning
confidence: 94%
“…The above results illustrated that subclinical changes in LV systolic function have occurred in athletes and MW indexes were more sensitive to provide early diagnosis value for LV performance among athletes [ 24 ]. According to the ROC analysis about LVMW parameters, GWE (AUC = 0.733) was considered of being the best predictor of LV systolic function in athletes and superior to GLS (AUC = 0.627) which was principally limited by the defect of being load-dependent and might lead to errors in judging LV performance [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cfPWV is a measure of arterial compliance, which is also determinant of stroke volume and thus CO. Finally, EF and E es have been reported to be positively correlated 46 and this further explains the high importance level of EF for predicting E es . The results using different subsets of the input features further verified each feature’s contribution to the predictions of the target output variables.…”
Section: Discussionmentioning
confidence: 75%